2022
DOI: 10.3350/cmh.2021.0193
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of chronic hepatitis C screening and treatment

Abstract: Hepatitis C virus (HCV) infection is the second most common cause of chronic liver disease in South Korea, with a prevalence ranging from 0.6% to 0.8%, and HCV infection incidence increases with age. The anti-HCV antibody test, which is cheaper than the HCV RNA assay, is widely used to screen for HCV infections; however, the underdiagnosis of HCV is a major barrier to the elimination of HCV infections. Although several risk factors have been associated with HCV infections, including intravenous drug use, blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…As a result, there is a need for a re‐evaluation of the global prevalence of HCV, as well as the staging and treatment of hepatitis in these populations. Previous studies have also emphasized the strong association between incarceration and injection drug use, which poses a significant risk for HCV transmission in correctional settings 12–14 . In our city, Guigang, from 2016 to 2021, a total of 6834 cases of hepatitis C have been reported in different districts, but only a small proportion of patients have received treatment.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…As a result, there is a need for a re‐evaluation of the global prevalence of HCV, as well as the staging and treatment of hepatitis in these populations. Previous studies have also emphasized the strong association between incarceration and injection drug use, which poses a significant risk for HCV transmission in correctional settings 12–14 . In our city, Guigang, from 2016 to 2021, a total of 6834 cases of hepatitis C have been reported in different districts, but only a small proportion of patients have received treatment.…”
Section: Introductionmentioning
confidence: 69%
“…A study in the United Kingdom showed that outreach services to homeless populations increased detection rates and recommended an immediate hepatitis C testing treatment strategy to increase treatment rates. To address inequalities in healthcare resources, a study in the United Kingdom [13] [15] showed that HCV clinic services in New York City were forced to be streamlined by the epidemic and that a combination of telemedicine and outpatient clinics is emerging as a new model for hepatitis C management. The results of another study [16] showed that telemedicine is an effective way to manage HCV drug-using populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The progression from HCV infection to the development of liver cancer is characterized by a gradual, protracted process that spans over 20–40 years in affected patients ( 9 ). Globally, in 2021, it was estimated that approximately 58 million people were living with chronic HCV infections ( 10 ). In the United States, the number of hepatocellular carcinoma cases due to HCV increased by 130% during 1990–1999 and 2000–2009 ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…HCV infection is a major chronic liver disease, with an estimated prevalence rate of 0.5% between 2012 and 2016 in Korea. Based on the genotype (GT) distribution, GT1 (52.7% of all infections) and GT2 (45.3%) were dominant in Korea [ 3 , 9 11 ]. More than 90% of the patients infected with HCV were over 40 years of age, and approximately 70% of the patients had chronic hepatitis, followed by 20% with LC [ 12 ].…”
Section: Introductionmentioning
confidence: 99%